Carbon Monoxide Dehydrogenase Activity in Bradyrhizobium japonicum - Lorite, María J. (American Society for Microbiology, 2000)
Bradyrhizobium japonicum strain 110spc4 was capable of chemolithoautotrophic growth with carbon monoxide (CO) as a sole energy and carbon source under aerobic conditions. The enzyme carbon monoxide dehydrogenase (CODH; EC 1.2.99.2) has been purified 21-fold, with a yield of 16% and a specific activity of 58 nmol of CO oxidized/min/mg of protein, by a procedure that involved differential ultracentrifugation, anion-exchange chromatography, hydrophobic interaction chromatography, and gel filtration. The purified enzyme gave a single protein and activity band on nondenaturing polyacrylamide gel electrophoresis and had a molecular mass of 230,000 Da. The 230-kDa enzyme was composed of large (L; 75-kDa), medium (M; 28.4-kDa), and small (S; 17.2-kDa) subunits occurring in heterohexameric (LMS)(2) subunit composition. The 75-kDa polypeptide exhibited immunological cross-reactivity with the large subunit of the CODH of Oligotropha carboxidovorans. The B. japonicum enzyme contained, per mole, 2.29 atoms of Mo, 7.96 atoms of Fe, 7.60 atoms of labile S, and 1.99 mol of flavin. Treatment of the enzyme with iodoacetamide yielded di(carboxamidomethyl)molybdopterin cytosine dinucleotide, identifying molybdopterin cytosine dinucleotide as the organic portion of the B. japonicum CODH molybdenum cofactor. The absorption spectrum of the purified enzyme was characteristic of a molybdenum-containing iron-sulfur flavoprotein.